Skema Digital Watermarking Citra dengan Metode TLDCT dan Chinese Remainder Theorem - Danang Aditya Nugraha; Rahmadwati; Muhammad Aziz Muslim (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Currently, it is easy to access the wide variety of digital content on the internet, and therefore protection effort for digital content is an important problem that needs to solve. One kind of digital content that urgently needs to protect is digital image. Protection is needed not only for the copyright but also for the authenticity of digital image because there are so many advanced image editing software, that are easy to use. This paper presents a scheme for digital image protection through Digital Watermarking process using Two Level Discrete Cosine Transform, and Chinese Remainder Theorem for color digital image. This scheme has an ability to detect and to recover some kind of changes that occur in the watermarked image. This ability can be achieved because this scheme is categorized into fragile digital watermarking, thus, has low robustness. However, based on experiment results, this scheme shows a good invisibility. It is higher than the previous research and has a minimum distortion, proven by Peak Signal to Noise Ratio (PSNR) value of around 45.